The Power of Minangkabau Pantun: A Media for The Development of Islamic Character of Students at Various Levels of Islamic Education in Indonesia - Dwi Septiani (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2021)
The purpose of this study is to explain that the Minangkabau pantun has the power as a medium for developing the Islamic character of students at various levels of Islamic education in Indonesia. Religious rhymes in the Minangkabau Oral Literature: Proverbs, Pantun, and Mantras as one of the effective media to develop the Islamic character of students at various levels of Islamic education in Indonesia. The method used in this study is a qualitative method with a descriptive approach. The primary data used in this study were 22 religious pantun. The results of this study are that this 22 religious pantun are closely related to philosophical values: Islam as the best religion, the implementation of the 5 pillars of Islam, and guidance to become human beings who act according to Islamic teachings in the Koran. Thus, it cannot be denied that this Minangkabau religious rhyme can be used as an effective medium to develop the Islamic character of students at various levels of Islamic education in Indonesia.